High density FTA plates serve as efficient long‐term sample storage for HLA genotyping. Issue 2 (7th January 2014) - Lange, V.; Arndt, K.; Schwarzelt, C.; Boehme, I.; Giani, A. S.; Schmidt, A. H.; Ehninger, G.; Wassmuth, R.
Abstract Storage of dried blood spots (DBS) on high‐density FTA® plates could constitute an appealing alternative to frozen storage. However, it remains controversial whether DBS are suitable for high‐resolution sequencing of human leukocyte antigen (HLA) alleles. Therefore, we extracted DNA from DBS that had been stored for up to 4 years, using six different methods. We identified those extraction methods that recovered sufficient high‐quality DNA for reliable high‐resolution HLA sequencing. Further, we confirmed that frozen whole blood samples that had been stored for several years can be transferred to filter paper without compromising HLA genotyping upon extraction. Concluding, DNA derived from high‐density FTA® plates is suitable for high‐resolution HLA sequencing, provided that appropriate extraction protocols are employed.